2021
DOI: 10.1029/2020jb020769
|View full text |Cite
|
Sign up to set email alerts
|

Eruptive Cycle and Bubble Trap of Strokkur Geyser, Iceland

Abstract: The eruption frequency of geysers can be studied easily on the surface. However, details of the internal structure including possible water and gas filled chambers feeding eruptions and the driving mechanisms often remain elusive. We used a multidisciplinary network of seismometers, video cameras, water pressure sensors and one tiltmeter to study the eruptive cycle, internal structure, and mechanisms driving the eruptive cycle of Strokkur geyser in June 2018. An eruptive cycle at Strokkur always consists of fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(69 citation statements)
references
References 43 publications
5
64
0
Order By: Relevance
“…This is observed in the Western part of the Hhf where lack of high vegetation mimics the boundaries of the highly resistive region (dashed black lines in Figure 9). The interpretation of this volume as a vapor-saturated reservoir would agree with Eibl et al (2020); Eibl et al (2021) who suggest the occurrence of a shallow bubble trap about 13-23 m West of Strokkur and at about 25-30 m depth. Figure 4 shows that the most prominent hydrothermal features of the Hhf are emplaced at the margins of highly resistive regions.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This is observed in the Western part of the Hhf where lack of high vegetation mimics the boundaries of the highly resistive region (dashed black lines in Figure 9). The interpretation of this volume as a vapor-saturated reservoir would agree with Eibl et al (2020); Eibl et al (2021) who suggest the occurrence of a shallow bubble trap about 13-23 m West of Strokkur and at about 25-30 m depth. Figure 4 shows that the most prominent hydrothermal features of the Hhf are emplaced at the margins of highly resistive regions.…”
Section: Discussionsupporting
confidence: 82%
“…It is suggested that Strokkur and Great Geysir geysers develop along vertical fracture-like pipes reaching at least 20 m depth (Pasvanoglu et al, 1998;Torfason & Davíðsson, 1985;Walter et al, 2018). Yet, besides indirect geophysical studies [e.g., Eibl et al (2020) and Eibl et al (2021)] little is known about the plumbing system at depth. Pasvanoglu et al (1998) propose that the ground water system of Hhf is recharged by meteoric waters flowing from the Langjöokull ice-sheet to the North.…”
mentioning
confidence: 99%
“…When the seismic source only releases a small amount of energy, and the distance of the source to the station is large, PE seems to reflect more the filtering of the seismic wave during its propagation to the station. This is also supported by the findings of Eibl et al (2021), who could not use these stations for the seismic source location due to low-quality particle motions. By contrast, the drop of PE prior to the 5.6 Mw earthquake at Bárðarbunga two days before the 1996 Gjálp eruption, could be detected by stations at a 100 km distance (Glynn & Konstantinou, 2016).…”
Section: The Influence Of Source Strength and Path Effects Toward The...supporting
confidence: 70%
“…The epicenters of the sources were estimated from the intersection of the azimuth angles derived from all 5 stations. Eibl et al (2021) project the epicenter location vertically down and extract the source depth from the intersection point with the derived incidence angles for all stations. Note that the shallow source depths during P1 and peaks in P4 are poorly constrained since the particle motion shows an elliptical particle motion characteristic for Rayleigh waves when the seismic sources reach or approach the surface.…”
Section: Stacked Pe Rms and Hypocentral Distances Of 53 Single Eruptionsmentioning
confidence: 99%
See 1 more Smart Citation